Phlebotrophic Effect of Graptophyllum Pictum (L.) Griff on Experimental Wistar Hemorrhoids - Mario Sadar Bernitho Hutagalung; Bernadus Parish Budiono; Sigit Adi Prasetyo; Ignatius Riwanto; Eriawan Agung Nugroho; Yan Wisnu Prajoko; Neni Susilaningsih (Journal of Biomedicine and Translational Research, 2019)
Background : The 1st and 2nd degree hemorrhoids is managed non-operatively with the anti-inflammatory and plebothropic drugs. Graptophyllum pictum extract (GPE) has already been used widely in Indonesia to treat hemorrhoid with good result, however, the mechanism is not supported by the molecular research.Objective : This study is intended to study the phlebothropic effects of GPE by measuring the degree of edema and extravassal leucocytes of experimental wistar hemorrhoid.Methods : Experimental study with Randomized Controlled Trial Post-test only design in male wistar rats, weight around 200 gr, induced for the development of a disease-like condition of hemorrhoids by 6% croton oil on the anus for 3 days. Random allocation was performed to divide the 14 wistar rats in 2 groups. Group I as control got normal saline solution, while group II was treated with GPE 100mg/kgbw, started on day 4th for 5 consecutive days. On 9th day blood was extracted from retroorbital fossa and anus was resected up to 2 cm from anal verge and weighted. The degree of anal edema was measured by rectoanal coefficient, that is rasio between anal weight (miligrams) and body weight (grams).Results : Until the end of study, all wistar rat were still alive. The mean (±SD) of body weight   of control group was 173.84 (±13.37) and the treatment group was 171.70  (±13.10), and there was no significant differences (p = 0.833). The mean (±SD) of rectoanal coefficient in the treatment group was 2.46 (±0.41) and it was significantly lower than control group  (3.13 ± 0.85) (p = 0.029). The mean (±SD) of extravassal leukocytes in the treatment group was 900.14(±48.09) and it was significantly lower than the control (1003.28 ± 99.30) (p = 0.042).Conclusions : Graptophyllum pictum extract at doses of 100 mg/Kgbw have phlebotonic effect  in decreased edema and extravassal leukocytes.